PEMANFAATAN E-MODUL BERBANTUAN VIRTUAL LABORATORY DALAM PEMBELAJARAN IPA MAHASISWA CALON GURU SEKOLAH DASAR DI MASA PANDEMI COVID-19 - Setyo Eko Atmojo (Universitas Negeri Medan, 2021)
The purpose of this study was to analyze the effectiveness of using virtual laboratory-assisted E-modules in science learning for prospective elementary school teacher students during the Covid-19 pandemic. This research method is an experiment with a quasi-experimental design. The subjects of this study were students of the PGSD study program FKIP UPY which consisted of two classes, namely class A5-20 as the experimental group and class A6-20 as the control group. The data collection instrument used a test question sheet consisting of pre-test and post-test question sheets. Data analysis technique using t-test and Normalized Gain (N-Gain). The results showed that there was a significant difference in science learning achievement between experimental group students and control group students as indicated by the value of t count = 2,799 > t table = 1,988 and (p) count = 0 < 0.05. Meanwhile, based on the results of the N-Gain test, it is known that the increase in science learning achievement in the experimental group obtained an N-Gain of 0.73 which is in the high category and in the control group an N-Gain of 0.52 is obtained which is in the medium category. Based on these results, it can be concluded that the use of e-modules assisted by virtual laboratories is effectively used in science learning for prospective elementary school teacher students during the COVID-19 pandemic.